Characteristics of The Compilation of Islamic Law In Indonesia: A Study of Marriage Law From The Perspective of Political Law - Aziz, Abdul (Sharia Journal and Education Center Publishing, 2024)
The Compilation of Islamic Law (KHI) in Indonesia serves as a normative guideline in the regulation of marriage law that integrates Islamic sharia values with existing social realities. However, the complexity of marriage issues in Indonesia, such as polygamy and child custody, shows the need for an in-depth study of the character and implications of KHI in the context of legal politics. This research aims to explore how KHI is formed and implemented, as well as its impact on society. This study uses a qualitative method with a descriptive approach of documentation analysis to explore the character of the Compilation of Islamic Law (KHI) and its implications for the practice of marriage law in Indonesia. The results show that the KHI functions not only as a formal regulation, but also as an instrument that reflects the aspirations of the community in achieving justice and welfare in family life. In addition, this finding emphasizes the importance of the involvement of the community and religious leaders in the KHI socialization process to overcome existing challenges, such as the protection of women's and children's rights. The conclusion of this study suggests the need for continuous evaluation of existing regulations in order to remain responsive to social dynamics, so that KHI can play an effective role in resolving marriage law problems in Indonesia. This research is expected to make a significant contribution to the development of Islamic law and legal practice in society, as well as strengthen the dialogue between law and social values.